Evaluation of TEMPO-NH2 and Oxalate Oxidase Enzyme for Complete Ethylene Glycol Oxidation - Antonio, Jesimiel Glaycon R.; Franco, Jefferson Honorio [UNESP]; Almeida, Paula Zaghetto de; Lourdes, Maria de; Polizeli, T. M.; Minteer, Shelley D.; Andrade, Adalgisa R. de [UNESP] (Wiley, 2022)
This study describes the development of an ethylene glycol (EG) biofuel cell that combines the organic catalyst 4-amino-TEMPO (TEMPO-NH2) and the enzyme oxalate oxidase (OxOx) in solution for complete EG oxidation. Cyclic voltammetric curves recorded in the presence of EG showed that the hybrid TEMPO-NH2/OxOx catalyst provided 1.2 higher current density than the TEMPO-NH2 catalyst. Chronoamperometric assays after successive EG injections and long-term electrolysis at a fixed potential of 0.75 V (vs Ag/AgCl) showed that the hybrid TEMPO-NH2/OxOx catalyst in the presence of EG promoted 14 % and 58 % increase in the current obtained with the TEMPO-NH2 catalyst, respectively. High-performance liquid chromatography (HPLC) results confirmed that TEMPO-NH2 and OxOx respectively acted on EG oxidation and C−C bond cleavage, leading to complete EG oxidation, harvesting all 10 of the EG electrons and high catalytic activity.
Keywords: Enzymatic biofuel cell; Ethylene glycol; Hybrid biofuel cell; Oxalate oxidase; TEMPO-NH2